Pirrit Hills subglacial bedrock core RB-2, cosmogenic Be-10, Al-26 data - Stone, John (IEDA: US Antarctic Program Data Center, 2019)
Abstract: This data set contains measurements of cosmic-ray-produced Be-10 and Al-26 in quartz from the RB-2 core, recovered from bedrock at a depth of 150 m below the West Antarctic Ice Sheet surface in the Pirrit Hills. The core site is located at latitude S81.09948, longitude W85.15694. Core length is approximately 8 meters. Lithology is A-type granite, similar in composition to bedrock exposed on nearby Harter Nunatak and other mountains in the Pirrit Hills (Lee et al. Geosci. J. 16, 421-433). Samples were processed at the University of Washington Cosmogenic Nuclide Laboratory. Chemical processing and purification methods are described at http://depts.washington.edu/cosmolab/chem.shtml. Beryllium isotope ratios were measured at the Lawrence Livermore Center for Accelerator Mass Spectrometry (LLNL-CAMS) relative to the KNSTD-Be-01-5-4 standard, assuming a standard Be-10/Be-9 ratio of 2.851E-12 (07KNSTD normalization). Aluminum isotope ratios were measured at PRIME Lab, Purdue University, relative to the KNSTD-Al-01-5-2 standard, assuming a standard Al-26/Al-27 ratio of 1.818E-12 (KNSTD normalization). Uncertainties are 1-sigma and include full AMS errors and all known sources of laboratory uncertainty.